Sintesis Biosurfaktan Dari Rubber Seed Oil Dan Trietanolamin : Pengaruh Temperatur Dan Waktu Reaksi - Adraf, Annisa Afrilla; Irdoni, Irdoni; Nirwana, Nirwana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The surfactant is a substance which has the ability to reduce surface tension, interface tension, and increase the stability of an emulsion. The Surfactant is an intermediate productwhich is widely applied in the fields of health, pharmacy, industry, and cleaning products in the household. This study makes biosurfactant from rubber seed oil. The purpose of this study is to make biosurfactants from rubber seed oil, to see the effect of temperature and time on the biosurfactant characterization produced. The preliminary treatment in this study includes preparation of raw materials, extraction of rubber seed oil by pressing method, the degumming process using phosphoric acid at temperature 90°C for 1 hour, gum separationby centrifuge. The esterification process of oil and methanol with a mole ratio of fatty acid: methanol (1:9), sulfuric acid catalyst (98%) as much as 1%(b/b) of oil, at temperature 65°C, the process is carried out until ALB < 2%. The transesterification process of methyl esterformation with a mole ratio of oil: methanol (1:9), KOH catalyst as much as 2%(b/b) of oil, at temperature 65°C for 6 hours. In the final stage, the transesterification process of methyl ester becomes esteramine with a mole ratio of methyl ester and trietanolamine (4:1), KOHcatalyst as much as 5%(b/b) of methyl ester, stirring speed 200 rpm, temperature variation 100°C; 125°C; 150°C, time variation during 2 hours; 4 hours; and 6 hours. The best characteristics of biosurfactant were produced at 100°C transesterification temperature and 6 hours transesterification time with the density of 0,906 gr/ml, the pH 9,8, the surface tension of 52 dyne/cm, the interface tension of 51,3 dyne/cm, the emulsion stability of 96,36%, the yield 88,480%, and FT-IR test to ascertain amine functional groups in biosurfactant.Keywords: Biosurfactant, rubber seed oil, transesterification, triethanolamine